Causal association of sex hormone-related traits with Alzheimer’s disease: a multivariable and network Mendelian randomization analysis - Zhang, Yan; Sun, Zhen-dong; Yang, Yu-shen; Fu, Wei-dong (Frontiers in Neurology, 2025)
BackgroundAlthough studies have demonstrated a correlation between sex hormone-related traits [such as sex hormone binding globulin (SHBG) and testosterone] and Alzheimer’s Disease (AD), the link remains uncertain due to the intricacies of AD pathology. The study aimed to investigate the possible causal link between sex hormone-related traits and AD.MethodsThe authors collected data from extensive genome-wide association studies (GWASs) of European ancestry on sex hormone-related traits and AD. Univariate and multivariate Mendelian randomization (MR) analyses were conducted to explore the possible causal relationship between these traits and AD. We used inverse variance weighted (IVW) MR as the main analysis.ResultsThe use of univariate MR-IVW revealed a possible causal relationship between SHBG [ORs (95% CI), 1.005 (1.001–1.009), p = 0.006], testosterone [ORs (95% CI), 0.994 (0.989–0.999), p = 0.013] and AD in female. There is no evidence of a causal association of SHBG [ORs (95% CI), 1.002 (0.999–1.005)), p = 0.237] and testosterone [ORs (95% CI), 1.000 (0.997–1.004), p = 0.810] with AD in males. Multivariate MR analysis revealed a possible direct causal connection between SHBG and testosterone in relation to females AD (SHBG-OR (95%CI), 1.005 (1.001–1.009, p = 0.023); testosterone-OR (95%CI), 0.995 (0.989–1.000, p = 0.049). Bidirectional MR analysis indicated that SHBG has a possible causal effect on testosterone (SHBG on testosterone-OR (95%CI), 1.064 (1.032–1.096), p = 0.0001). The results of the network MR analysis suggested that testosterone may act as a mediator in the causal pathway from SHBG to AD.ConclusionOur study using the MR methodology indicates that increase of SHBG level and decrease of testosterone level in females are positively linked to an increased risk of developing AD. Importantly, testosterone plays a mediating role in the causal pathway from SHBG to females AD.